Optimisation of seed germination and seedling emergence of sesbania cannabina (retz.) Poir. (Bangladesh Journal of Botany, 2023)
This study aims to optimise the condition for seed germination and seedling emergence of Sesbania cannabina (Retz.) Poir. for a phytoremediation study. In this experiment, seed germination was carried out using two growth media: Murashige and Skoog basal medium (MS); and Whatman Grad 1 filter paper (FP), using the top of media or top of the paper method under three different photoperiods. Seeds were pre-treated for different lengths of time with various concentrations of hydrogen peroxide (H2O2) (v/v) multiple hot water treatments. Results showed that seeds pre-treated with H2O2 (6% v/v) for 5 minutes and primed with 65°C water for 5 minutes were considered as the ideal pre-treatment condition. Different photoperiods and media used in germination in this experiment do not significantly affect seed germination. The optimum condition for seed germination at 27.5 °C ± 2.5°C and relative humidity of ~ 75% for 5 days. Seed emergence in soil and compost was significantly affected by the burial depth and bulk density of the media, with the highest (98%±1) seed emergence observed at 1 cm depth for soil and compost, and decreasing with increased burial depth. This ideal condition will help in further studies related to plant growth and phytoremediation of S. cannabina.Bangladesh J. Bot. 52(4): 1015-1023, 2023 (December)